2016
DOI: 10.1371/journal.pone.0166893
|View full text |Cite
|
Sign up to set email alerts
|

Role of Platelet Parameters on Neovascular Glaucoma: A Retrospective Case-Control Study in China

Abstract: PurposeRetinal vein occlusion (RVO) and diabetic retinopathy (DR) are two major sight-threatening diseases which may lead to neovascular glaucoma (NVG). The aim of this study was to explore the association between platelet parameters and NVG.MethodsA total of 185 subjects were enrolled for the study from January, 2012 to December, 2015 at the Eye-ENT Hospital of Fudan University. Patients include those with NVG secondary to RVO (RVO group, n = 38), patients with NVG secondary to DR (DR group, n = 47), diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A total of 12 articles with 1681 patients explored the relationship between PDW and DR [ 21 , 23 , 32 , 50 , 58–60 , 65 , 67–69 , 71 ]. Considering the significant heterogeneity amongst the 12 studies ( I 2 = 79.3; P <0.01), random-effect model was applied when we performed the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 articles with 1681 patients explored the relationship between PDW and DR [ 21 , 23 , 32 , 50 , 58–60 , 65 , 67–69 , 71 ]. Considering the significant heterogeneity amongst the 12 studies ( I 2 = 79.3; P <0.01), random-effect model was applied when we performed the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…After duplicates were removed, only 42 full-text studies were evaluated. After exclusion of review and no-related articles, a total of 14 studies [ 10 – 23 ] were included in the final meta-analysis according to the inclusion criteria, including 2 cross-section studies [ 10 , 14 ] and 11 case control studies [ 11 13 , 15 23 ]. There are 1252 cases in the DR group, 1359 cases in T2DM without DR group and 1133 cases in control group.…”
Section: Resultsmentioning
confidence: 99%
“…Measuring platelet parameters, which can partially imply platelet function and activation, has been widely used to evaluate disease development and progression [12, 13]. Our previous study reported that mean platelet distribution width (PDW) and mean platelet volume (MPV), both of which are markers of platelet activation, were increased in patients with neovascular glaucoma and primary angle-closure glaucoma [14, 15]. To our knowledge, no previous study has investigated the association between platelet parameter and POAG.…”
Section: Introductionmentioning
confidence: 99%